Uso de plasma sanguíneo porcino en productos cárnicos emulsificados cocidos para mejorar la retención de agua - Sarmiento Ruiz, Dayana Carolina; Neira Silva, Jean Pierre (My University, 2024)
In the present thesis work, the effect of incorporating porcine blood plasma in sausages with different concentrations of porcine plasma (1%, 3% and 5%) was investigated, evaluating its water retention capacity, yield and changes in its physicochemical composition by means of bromatological analysis, determining the content of proteins, fats, moisture, ash and pH. In parallel, a sensory analysis was carried out based on descriptors such as colour, smoky odour, pork aroma, flavour, hardness, juiciness, cohesiveness and chewiness, as well as the general acceptability of the products. The results indicated that the incorporation of porcine blood plasma significantly improved (p<0.05) the water holding capacity of the sausage, reducing mass losses and improving the yield of the finished product. The sausage containing 5% blood plasma exhibited the highest water retention capacity. Sensory analysis showed that the sausage without plasma (standard) was the most acceptable. The bromatological results indicate that the best performing sample complies with the standards for cooked meat products.
En el presente trabajo de titulación se investigó el efecto de la incorporación de plasma sanguíneo porcino en embutidos con diferentes concentraciones de plasma porcino (1%, 3% y 5%), evaluando su capacidad de retención de agua, rendimiento y los cambios en su composición fisicoquímica mediante análisis bromatológicos, determinando el contenido de proteínas, grasas, humedad, cenizas y pH. Paralelamente, se realizó un análisis sensorial basado en descriptores como color, olor ahumado, aroma a carne de cerdo, sabor, dureza, jugosidad, cohesividad y masticabilidad, además de la aceptación general de los productos. Los resultados indicaron que la incorporación de plasma sanguíneo porcino mejoró significativamente (p<0,05) la capacidad de retención de agua del chorizo, reduciendo las pérdidas de masa y favoreciendo el rendimiento del producto terminado. El embutido con 5 % de plasma sanguíneo presentó la mejor capacidad de retención de agua. El análisis sensorial demostró que el embutido sin plasma (patrón) fue el más aceptado. Los resultados bromatológicos indican que la muestra con mejor resultado cumple con las normas para productos cárnicos cocidos.
Keywords: EMBUTIDO; CAPACIDAD DE RETENCIÓN DE AGUA; PLASMA SANGUÍNEO PORCINO; ANÁLISIS SENSORIAL; BROMATOLOGÍA